Processes of Artistic Expression and Development in the Novel Genre - Sultonova Nilufar Narzullaevna, (European Journal of Life Safety and Stability (2660-9630), 2024)
In the article, the principles of character creation and expression of the unique image of heroes in recent years in Uzbek prose, especially in Uzbek novels, have been researched.